PERAN MEDIA MASSA TERHADAP PEMILIH PEMULA DALAM PEMILU PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 - Sulistiyo, Budi; Suwartiningsih, Sri (KRITIS, 2018)
The term novice voters are regarded toHigh School Students, College Students, or worker who is between 17 to 21 years old and never been participate or vote in the election. This definition is hand in hand with the law number 10 - 2008, regarding genera election that define the minimum or condition of the voter (article 19:1). Novice voters are characterized as educated, critical, independent, fashionable, adaptable, and like to learn new things. Before the Indonesia Presidential Election in 2014, the media were intensively relay informations on the president and vice president candidates. The media have important part indelivering information and knowledge for the citizens about the election. Newspaper, magazines, radio and television are believed to be the most vital part in the politic democracy system.The study used the Kultivation Theory Analysis, which focus on how the influence of media to the citizens through the news that were broadcasted in the television continuously. This is a descriptive qualitative study which means to describe the role of media especially television that affect the perspective and the novice voters’ attitude toward 2014 the presidential election. The result of this study showed that the role of television staton, especially the Metro TV and TV One were vital, because novice voters whit their limited knowledge about election, gain informations through those Metro TV and TV One to gain knowledge and information about the 2014 presidential election. As the result, the media is capable to affect the novice voters’ point of view to actively participate as voters in the 2014 presidential election.